The effects of using karaoke videos on Malaysian JFL students' vocabulary learning - Abdullah, Muhammad Alif Redzuan; Hussin, Sanimah (City University of Hong Kong Press, 2022)
This research paper aimed to explore and investigate whether the use of karaoke videos in Japanese language classes influences vocabulary acquisition among Malaysian Japanese language learners. The study was conducted on 150 students learning Japanese at the beginner level as an elective subject at the Faculty of Modern Languages and Communication, Universiti Putra Malaysia (UPM). Data were collected through questionnaires, interviews, and observations. The analytical descriptive results showed that the participants could memorize and understand Japanese vocabulary quickly and easily after watching karaoke videos that contained visual graphics/animations combined with text, which stimulate their brains. Data from the interviews also showed that the target vocabulary items were pronounced accurately and correctly when learners sang along while watching the karaoke videos. The triangulation of data showed that karaoke videos are a good tool to engage participants in learning Japanese while having fun; this has resulted in higher motivation when learning the language. This study asserts that the use of karaoke videos in other foreign language classes will help boost students’ confidence and motivation levels. Students were more engaged when songs with basic Japanese vocabulary were used in the lesson because the songs offered context-specific, individualized appeal and memory help for essential ideas. Songs are significant from a constructivist perspective because they help students generate meaning, from a sociocultural perspective in terms of student participation, and from a cognitive standpoint because they assist students to establish connections in learning in these cases.